The lime green secret - Graham, Georgia (Plattsburgh, N.Y. : Tundra Books of Northern New York, 2009)
Gloria is unable to keep her hands off the beautiful dress she is supposed to wear at her sister's wedding, but disaster strikes when she accidently spills lime soda on the gown while having tea with her animal friends, and she must come up with a creative way to hide the stain.
Resource Links.
4.2
K-3
Keywords: Dresses -- Juvenile fiction; Weddings -- Juvenile fiction; Dresses -- Fiction; Weddings -- Fiction; Dresses -- Fiction; Weddings -- Fiction